1999
DOI: 10.1021/bi991664s
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Preliminary Characterization of the Na+-Translocating NADH:Ubiquinone Oxidoreductase from Vibrio harveyi

Abstract: The Na(+)-translocating NADH: ubiquinone oxidoreductase (Na(+)-NQR) generates an electrochemical Na(+) potential driven by aerobic respiration. Previous studies on the enzyme from Vibrio alginolyticus have shown that the Na(+)-NQR has six subunits, and it is known to contain FAD and an FeS center as redox cofactors. In the current work, the enzyme from the marine bacterium Vibrio harveyi has been purified and characterized. In addition to FAD, a second flavin, tentatively identified as FMN, was discovered to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 35 publications
8
108
0
1
Order By: Relevance
“…A similar analysis showed that riboflavin is present also in Na ϩ -NQR purified from the bacterium Vibrio harveyi (ref. 9 and data not shown), which demonstrates that the riboflavin cofactor is not limited to the enzyme from V. cholerae.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…A similar analysis showed that riboflavin is present also in Na ϩ -NQR purified from the bacterium Vibrio harveyi (ref. 9 and data not shown), which demonstrates that the riboflavin cofactor is not limited to the enzyme from V. cholerae.…”
Section: Resultsmentioning
confidence: 70%
“…Recombinant Na ϩ -NQR from V. cholerae was purified according to a protocol described before (10). The V. harveyi Na ϩ -NQR was prepared as described (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of NosR from Paracoccus denitrificans shows agreement with the described topology (R. J. M. van Spanning, The flavin-binding domain of NosR is found in, among other proteins, the NqrC subunit of the Na ϩ -translocating NADH: quinone oxidoreductase of the genus Vibrio. NqrC was shown to carry FMN covalently bound as a phosphodiester to a threonine residue (17,27,52). Given the spectral evidence and the supporting flavin-binding consensus sequence, we suggest that NosR of P. stutzeri carries a flavin cofactor covalently bound to T163.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, motifs for the binding of flavin and NADH were identified on NqrF (14). Subunits NqrB and NqrC each contain one FMN that is covalently linked to a threonine residue (15)(16)(17). Recently, riboflavin was identified as a component of the Na ϩ -NQR complex from V. cholerae (18).…”
mentioning
confidence: 99%